Keberkesanan Aplikasi Pemodelan Maklumat Bangunan (BIM) Dalam Mengatasi Masalah Kelewatan Projek - Abu Yazidyusnisab, Muhammad Hamizan; Masrom, Md Asrul Nasid; Yahya, Mohd Yamani; Shafii, Haryati (Research in Management of Technology and Business, 2024)
Building Information Modeling (BIM) is a recent approach in the construction industry that uses 3D digital models to plan, build, and manage projects. BIM is seen to help and have a positive effect in dealing with the problem of project delays. BIM can help reduce project delays by minimizing errors in design aspects, speeding up changes and adaptations and resource management. The use of this technology also increases the effectiveness and efficiency in project implementation. Although BIM is able to reduce the problem of delays in construction projects, studies focusing on this matter are still lacking. Therefore, this study was conducted to achieve objectives such as identifying the factors of project delays in Malaysia, examining the level of implementation of Building Information Modeling (BIM) in projects in Malaysia, and examining the effectiveness of implementing Building Information Modeling (BIM) in overcoming project delays in Malaysia. This study uses a qualitative method through interviews. The selected respondents are construction industry players who are active and have used BIM in Malaysia. The findings of the study show that the factors that cause project delays in Malaysia are design changes, authority obstacles, lack of manpower, site planning and design change factors are factors that often occur. In addition, the level of BIM implementation in projects in Malaysia is still low except at the construction stage. Next, BIM is effective in overcoming project delays in Malaysia from the perspective of collaborative work, communication, schedule management, and monitoring. This study is expected to help industry players to be more clear about BIM practices and how it can overcome project delays. The results of this study are also expected to help reduce project time, cost, and risk.